Sistem Pendukung Keputusan Pemilihan Wakil Kepala Sekolah Di SMPN 47 Bandung Menggunakan Metode Multi-Objective Optimization by Ratio Analysis (MOORA) - Asep Syaipul Iman; Gunawansyah (Universitas Islam Raden Rahmat, Malang, 2023)
In an organization, a change of leadership is a common thing. Often, the process of changing leadership results in decisions that are not objective, transparent, and accountable, so they have a negative impact on the organization. The change of leadership, particularly in the school environment, is usually accomplished through voting in the election of the Deputy Principal. This system has a weakness because the selection is made without clear assessment indicators. As a solution in the current era of information technology, the use of a decision support system is one of the ways to overcome the above problems so that the resulting decisions will be more objective, transparent, and accountable. The decision support system used in this study uses the MOORA method because this method has high flexibility and good selectivity. The Deputy Principal Election Decision Support System application is designed to be web-based so that it can be accessed from anywhere without distance or time constraints. The application of this system can produce decisions that are more objective, transparent, and accountable.